Mechanical Design and Motion Analysis of a Hybrid Robot for Equine Rehabilitation - YE Zenglin; DAI Zhonghong; ZHANG Liang'an; WEI Liangguo; CHEN Hua (工程科学与技术)
ObjectiveEquine therapy, also referred to as therapeutic riding or equine-assisted therapy, is a clinical methodology that promotes physical, psychological, and social functioning through the integration of horse handling and riding skills. It is generally overseen by a qualified therapist or equestrian instructor, and serves as a rehabilitation tool amalgamating equine and therapeutic techniques to alleviate conditions such as cerebral palsy and autism. Whilst equine therapy has demonstrated efficacy in rehabilitating particular conditions, its dissemination is impeded by several constraints and challenges. Furthermore, equine therapy presents a number of limitations and challenges. High expenses, specialised facilities, and the specificity of horses impede the implementation of the therapy on a broader scale. Furthermore, challenges related to individual variations and the requirement for specialised therapist training need to be addressed, alongside cost, resource, and training concerns, to ensure wider adoption of equine therapy. To promote its application, an alternative to conventional biological equine exercise rehabilitation therapy could be a horse-riding rehabilitation robot. Such a development could improve the accessibility and effectiveness of equine therapy on a broader scale. The horse saddle during various gaits involves four primary movements: up and down, forwards and backwards, left and right tilting, and forward and backward tilting. These movements are integral to understanding the saddle’s function. Clear conceptualization of these movements is essential for riding and safely using the horse saddle.MethodsTherefore, the robot horse mechanism must possess the four degrees of freedom mentioned earlier. The high load and stiffness requirements when accommodating a person have been taken into account in the design process. As a result, a 3-RPS parallel mechanism is selected as the primary component, capable of carrying out up-and-down movement, left-right tilt, and forward-backward tilt of the saddle. The sketch of the mechanism is demonstrated in Fig. The saddle’s forward-and-backward movement is achieved through one moving vice, while another facilitates the up-and-down and back-and-forth movements. To reduce load and inertia, the mobile vice is mounted on the parallel mechanism’s moving platform. Together, the parallel mechanism and mobile vice comprise a 3-RPS-P hybrid robot. The mechanism possesses excellent stiffness, high load-carrying capacity, and remarkable flexibility, fulfilling the requirements for the saddle centre’s movement during rehabilitation therapy and load carrying capacity during horse riding. Firstly, the robot’s kinematic model was established, followed by deriving the analytical solution for the inverse kinematics. The positive kinematics solution was then obtained by utilising Newton’s iterative computation method. The relationship between the robot’s operational space and the joint space velocity Jacobian was investigated. Additionally, the robot’s workspace was analysed while considering the restriction of motion, and a spatial image was plotted accordingly. Finally, using Lagrange’s method, the dynamics of the parallel mechanism were established. Next, an examination is conducted on the correlation between the motion of the mechanism and the force applied. The motion theories outlined above have been compared and analyzed through examples, and the results have confirmed their validity and accuracy. These theories have then been transferred into MATLAB code, and the robot end’s path and trajectory planning and design have been carried out.Results and DiscussionsA joint motion simulation of the robot utilizing the SolidWorks Motion module has also been conducted, demonstrating a consistent and smooth trajectory in line with the planning and design objectives. This simulation showcases the robot’s ability to successfully attain its set goals and objectives. The simulation is seamlessly executed and aligns with the planned and designed objectives, demonstrating the robot’s capability to accomplish the designated position-planning motion. Furthermore, it verifies the theoretical analysis outcomes. Finally, the experimental platform for the horse-riding rehabilitation robot was established in order to conduct motion experiments for position planning in motion simulation. The experimental results confirmed the rationality of the mechanism, attained the intended motion trajectory, and showcased rapid response of the control system. Due to the complexity of its calculations, the kinematics of the positive solution is time-consuming, taking 2~3 ms. However, as the display and monitoring meet usage requirements, this signifies that the hybrid horse rehabilitation robot possesses the necessary movement ability for equestrian therapy.ConclusionsThe locomotive behavior of horses in various gaits, including fast walking, running, and jumping, will be further examined through the study of the robot. To analyse the impact of varying movement gaits, amplitudes and speeds on rehabilitation therapy and optimise mechanism and motion control with input from equestrian therapists’ riding feedback and suggestions. Additionally, establish a real-time feedback system within the machine’s simulation of horse movement to monitor and adjust the robot's motion status. To assess the effectiveness of robotic horse rehabilitation therapy, the performance and recovery of the experimental group will be compared to that of the control group. Furthermore, safety and stability will be prioritized in the mechanism and motion control design to prevent falls and potential injuries to users during rehabilitation therapy.